Rethinking while Redoing: Tactical Affordances of Assistive Technologies in Photography by the Visually Impaired - Vendela Grundell (Media Theory)
This article addresses ableism in 21st century netÂwork society by analysing affordÂances in the practices of visually impaired photographers. The case study details how these photoÂgraphers use assistive deÂvices, tweaking affordÂances of both these devices and the photoÂgraphic apparatus: its techÂnical materialities, cultural conceptÂualÂizations and creative exÂpressions. The main argument is that affordances operate in exÂchanges where sharing differÂences is key; visually imÂpaired photoÂgraphers make differÂÂences sharable through images, revealing vulnerÂabilities that emerge within a socio-digital condition that affects users across a spectrum of abiliÂties. The argument unfolds through a rare combination of affordance theory about imaginative and diÂverse human-technology reÂlaÂtions, media theory about technological deÂpenÂdÂence and disÂÂruption, disability studies on normÂÂaÂtivity and variÂation, and art histoÂrical readÂings informed by semiotics and phenoÂmenÂoÂlogy. The article conÂtributes to cross-disciplinary research by demonÂstrating that affordances can be tactical, inÂterÂvening in pervasive socio-digital systems that limit who counts as a normal user.